SOLUTION
From the line
![y=-2x-4](https://img.qammunity.org/2023/formulas/mathematics/college/pop9baacilvj9e4gk8pagxlz7q8tf8nt8g.png)
Comparing this to equation of a line in the form of
![y=mx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/r9wr7tk2q8cfcans6j0owflua8au85op0h.png)
m= -2.
Let this be the first slope. Hence
![m_1=-2](https://img.qammunity.org/2023/formulas/mathematics/college/u4cybcds6apm92xbu6q0zxolifr45eb1z3.png)
When two lines are perpendicular, their slope is related by the formula
![m_1* m_2=-1](https://img.qammunity.org/2023/formulas/mathematics/college/drvgj3vmsiwqhbbe0hcgk6m0betp6bgxci.png)
From here, we have that
![\begin{gathered} m_1* m_2=-1 \\ -2_{}* m_2=-1 \\ m_2=(-1)/(-2) \\ m_2=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mbpgzhvgjsuc533km96iw0cz0uqxd8yvih.png)
Equation of a line in lope-intercept form is give as
![\begin{gathered} y-y_1=m(x-x_1) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bduwfme3p7y5g0tpnhx4b6k652qbmb39va.png)
Using m2 to represent m in the equation we have
![\begin{gathered} y-y_1=m(x-x_1) \\ y-y_1=m_2(x-x_1) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s1xpkea1gt2yidzwm5cnc8inhb2y454uq6.png)
Where y1 = 4 and x1 = 3, our equation becomes
![\begin{gathered} y-y_1=m_2(x-x_1) \\ y-4_{}=(1)/(2)_{}(x-3_{}) \\ y-4_{}=(1)/(2)_{}x-(3)/(2) \\ y=(1)/(2)_{}x-(3)/(2)+4 \\ y=(1)/(2)_{}x+(5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6u8lgpz228xq21d6a1h2cs78e6ld5vg8v5.png)
Hence the answer is
![y=(1)/(2)_{}x+(5)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/wc39uxwljw17d6ooocrbax816ke010otam.png)